2004
DOI: 10.1164/rccm.200404-533oc
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory Oligonucleotides Attenuate Airways Remodeling in Allergic Monkeys

Abstract: To determine whether inhaled immunostimulatory DNA sequence oligonucleotides containing CpG motifs mitigate the pathophysiologic manifestation of the asthmatic phenotype (airways hyperresponsiveness and airways remodeling), rhesus monkeys with experimentally induced allergic airways disease were treated seven times with inhaled immunostimulatory oligonucleotides (or sham) periodically for 33 weeks. Airways hyperresponsiveness was reduced twofold in immunostimulatory DNA sequence-treated compared with sham-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 23 publications
(35 reference statements)
1
37
0
Order By: Relevance
“…In limited studies in mild asthmatics utilizing an allergen challenge study design, nebulized ISS did not reduce the number of sputum eosinophils or the late-phase response to allergen challenge [45] . Thus, further studies are needed to determine whether ISS, which has demonstrated therapeutic efficacy in mouse [19][20][21][22][23][24] and primate models of asthma [46] , is effective in humans with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…In limited studies in mild asthmatics utilizing an allergen challenge study design, nebulized ISS did not reduce the number of sputum eosinophils or the late-phase response to allergen challenge [45] . Thus, further studies are needed to determine whether ISS, which has demonstrated therapeutic efficacy in mouse [19][20][21][22][23][24] and primate models of asthma [46] , is effective in humans with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…TLR9 agonists (i.e., ISS-ODN, also known as CpG-ODN) are potent inhibitors of experimental asthma in rodents (35)(36)(37) and primates (38). This inhibition is transient and lasts for 6 wk (39).…”
Section: Administration Of Iss-odn Prevents Th2 Phenotype Spreadmentioning
confidence: 99%
“…ISS acutely inhibits Th2-mediated airway inflammation by inhibiting local lung antigen-presenting cell costimulatory molecule expression and by preventing Th2 cytokine release from airway Th2 cells, basophils, and/or mast cells, highlighting the functional importance of ISS delivery to the airways (9). ISS efficacy in mouse models of asthma has been subsequently confirmed in rhesus monkeys in which inhaled ISS suppresses airway hyperresponsiveness and cellular inflammation in the lung tissue (10). Importantly, recent clinical studies have demonstrated potential for ISS-allergen conjugate therapy in human allergic airways disease (11)(12)(13).…”
Section: Introductionmentioning
confidence: 97%